Paradigm of Integration and Islamization of Science: Implementation in Islamic Higher Education - Mhd Miftachuddin Rasyid Nasution; Rustam Ibrahim (Lembaga Yasin AlSys, 2026)
Although the Islamic worldview, knowledge integration, and the Islamization of knowledge have received considerable scholarly attention, research specifically examining their implementation as a comprehensive strategy for addressing contemporary intellectual challenges in Islamic higher education remains limited. This study aimed to analyze the role of Islamic higher education institutions in implementing knowledge integration and Islamization as an effort to strengthen the Islamic worldview and reconstruct the relationship between religious and scientific disciplines. A qualitative approach with a library research design was employed, drawing on scholarly sources, including books, journal articles, and academic publications relevant to the Islamic worldview, knowledge integration, the Islamization of knowledge, and Islamic higher education. Data were collected through documentation techniques and analyzed using content analysis. The findings indicate that the decline of Islamic civilization is partly associated with the dichotomous separation between religion and science, which has produced fragmented knowledge and limited interdisciplinary engagement. The study further reveals that the implementation of knowledge integration and Islamization in Islamic universities can be pursued through two main strategies: curriculum reconstruction grounded in Islamic values, the Islamic worldview, and the dewesternization of knowledge; and the implementation of a boarding system that integrates intellectual, spiritual, and moral development. These strategies support the formation of graduates who possess intellectual competence, spiritual awareness, and ethical character rooted in the principle of Tawhid. The study concludes that integrating Islamic values into academic systems and institutional culture is essential for strengthening students’ intellectual and spiritual capacities. These findings contribute to Islamic educational philosophy by extending the discourse on the integration of religious and scientific knowledge, while offering practical implications for Islamic higher education institutions in designing curricula, educational policies, and student development programs aligned with Islamic principles. Future research may further examine empirical models for implementing knowledge integration and Islamization in contemporary Islamic universities. Keywords: Islamic Worldview; Knowledge Integration; Islamization of Knowledge; Islamic Higher Education; Tawhid